Unconventional cyclotron resonance in the organic superconductor beta''-(ET)(2)SF2CH2CF2SO3 - Edwards, R; Symington, J; Rzepniewski, E; Ardavan, A; Singleton, J; Schlueter, J (2001)
We have measured angle-dependent magnetoresistance oscillations and the interplane millimetre-wave conductivity of the organic superconductor beta "-(ET)(2)SF5CH2CF2SO3 as a function of the orientation of the applied magnetic field. We observe harmonics of the cyclotron frequency in the real-space velocity of quasiparticles orbiting the Fermi surface (FS). The harmonic amplitudes depend on the field orientation, providing a new way to measure the quasi-two-dimensional FS topology.